Advances in artificial intelligence applications - Puteh Saad author; Hishammuddin Asmuni editor; Nor Bahiah Ahmad author; Mariyam Shamsuddin author; Ruhaidah Samsudin author; Ani Shabri author; Nursafawati Mahshos author; Subariah Ibrahim author; Rusni Darius author; E. Mohebi author; Mohd. Noor Md. Sap author; Ali Selamat author; et al. (Skudai : Universiti Teknologi Malaysia, 2008)
Includes bibliographical references and index